Genetic diversity of mangoes (Mangifera indica L.) and its relatives in Seliu Island, Belitung District, Indonesia based on Inter-Simple Sequence Repeat markers - DENIA DWI CITRA RESMI; TATIK CHIKMAWATI; NINA RATNA DJUITA; MIFTAHUL HUDA FENDIYANTO; DEWI RAHMAWATI (Society for Indonesian Biodiversity, 2024)
Abstract. Resmi DDC, Chikmawati T, Djuita NR, Fendiyanto MH, Rahmawati D. 2024. Genetic diversity of mango (Mangifera indica L.) and its relatives in Seliu Island, Belitung District, Indonesia based on Inter-Simple Sequence Repeat markers. Biodiversitas 25: 4253-4264. Seliu Island is known as a mango island, but information on their identity, taxonomic status, and abundance of mango variety on this island has yet to be recorded. This study aimed to identify the genetic diversity of mangoes on Seliu Island. Fifteen Inter-Simple Sequence Repeat (ISSR) primers were used to profile the genetic diversity of 49 mango accessions from Seliu Island. The selected primers produced 193 polymorphic bands out of 222 (86.17%). All mango accessions on Seliu Island were identified and can be classified into eight species: Mangifera indica, Mangifera laurina, Mangifera zeylanica, Mangifera magnifica, Mangifera quadrifida, Mangifera caesia, Mangifera odorata, and Mangifera foetida. The genetic diversity among species was high, with a Shannon's information index of 0.334 and expected heterozygosity of 0.210. The unweighted pair group method with arithmetic average (UPGMA) dendrogram was created using a simple matching method, and all accessions were grouped into two main clusters according to their subgenus, Limus (Marchand) Kosterm and Mangifera. All accessions are also grouped according to their species. This study shows that the accessions from Seliu Island and West Java tend to cluster based on geographical origin. The study of mango genetic diversity using ISSR markers provided valuable information on the genetic relationships and variability among local mango cultivars on Seliu Island. This information can be used for breeding programs, conservation, and developing mango varieties.